Gender and Statelessness in Lebanon: The Missing Conversation in Protection and Humanitarian Programming - Nooreddine, Duaa (2025)
This thesis explores the intersection of gender and statelessness in Lebanon. Through a qualitative, expert-informed research design, the study asks “How does gender influence protection for stateless people in Lebanon?” This overarching question is addressed by investigating the following three issues: (1) the extent to which organizations working on statelessness incorporate gender considerations into their programming; (2) whether gender is seen as a significant factor in the protection of stateless individuals; and (3) the presence or absence of collaboration between statelessness-focused and gender-focused organizations. The research draws on 15 semi-structured interviews with program managers, legal advocates, gender experts, and caseworkers from organizations operating in Lebanon, as well as a review of organizational documents and publications such as program brochures and project reports. The results showed that gender is predominantly absent as both consideration and intervention in stateless-focused interviews. In addition, key findings revealed that most statelessness-focused actors frame statelessness primarily as a technical or legal issue, resulting in gender being deprioritized or treated as a secondary concern. While some practitioners acknowledged the gendered impact of statelessness, these insights rarely translated into gender-sensitive program design. Findings also highlighted the lack of formal referral pathways, sectoral coordination, or shared frameworks between gender and statelessness actors, reinforcing what this study terms a “missing conversation”. The thesis concludes that addressing statelessness without integrating gender considerations perpetuates exclusion and limits the effectiveness of protection responses. It calls for intentional, cross-sectoral collaboration and the incorporation of intersectional approaches to ensure more inclusive and responsive humanitarian programming.